Partisipasi Perempuan Indonesia dalam Ekonomi Kreatif untuk Mewujudkan Sustainable Development Goals - Idrina Nur Khairunnisa; Ika Riswanti Putranti; Marten Hanura (Journal of International Relations, 2022)
The participation of women in the development process is important in achieving the targets of the Sustainable Development Goals (SDGs). Through their participation, women can support the success of the SDGs as well as encourage a country's economic growth. The creative economy is a sector that the Indonesian government has chosen to increase women's participation. Although the Government has succeeded in making women the main actors in the creative economy, in fact, the efforts made by the Government are not enough because women are still faced a number of vulnerabilities. With this background, this research is aimed to discuss why women's participation in the creative economy in Indonesia has not been maximized to achieve the SDGs through the Gender and Development framework. Furthermore, this research will also look at the fulfillment of the practical needs and strategic interests of women who participate in the creative economy. This research uses a qualitative method with sources obtained from literature studies and interviews. Based on the research that has been done, it was found that the main causes that women's participation has not been maximized to achieve the SDGs through the creative economy are the social construction of gender and the unfulfilled practical needs and strategic interests of women.